2020
DOI: 10.3390/met10091215
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PWHT of Simulated HAZ Subzones in P91 Steel with Respect to Hardness and Impact Toughness

Abstract: Appropriate post weld heat treatment (PWHT) is usually obligatory when creep resistant steels are welded for thermal power plant components that operate at elevated temperatures for 30-40 years. The influence of different PWHTs on the microstructure, hardness, and impact toughness of simulated heat affected zone (HAZ) subzones was studied. Thereby, coarse grained HAZ, two different fine grained HAZ areas, and intercritical HAZ were subjected to 20 different PWHTs at temperatures 740–800 °C and durations 0.5–8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…(2) Finally, the welded component is subjected to the post weld heat treatment (PWHT). It is performed at temperatures ≥ 700 °C [2,5,6] to reduce the welding residual stresses and to induce the desired metallurgical effects like partial dissolution of carbides and tempering of Recommended for publication by Commission IX -Behaviour of Metals Subjected to Welding martensite that typically improve the mechanical properties (toughness, i.e., higher fracture resistance. )…”
Section: Welding Of 9% Cr Steelsmentioning
confidence: 99%
“…(2) Finally, the welded component is subjected to the post weld heat treatment (PWHT). It is performed at temperatures ≥ 700 °C [2,5,6] to reduce the welding residual stresses and to induce the desired metallurgical effects like partial dissolution of carbides and tempering of Recommended for publication by Commission IX -Behaviour of Metals Subjected to Welding martensite that typically improve the mechanical properties (toughness, i.e., higher fracture resistance. )…”
Section: Welding Of 9% Cr Steelsmentioning
confidence: 99%
“…Improvements in properties and the study of crack behavior of dynamically loaded materials and weld joints in a variety of steel types has attracted the attention of numerous authors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In previous research [ 16 ] on martensitic steel P91, it was found that in the as-welded condition, the IC HAZ (intercritical HAZ) exhibited significantly higher impact toughness than the FG HAZ (fine-grained HAZ), while in the CG HAZ (coarse-grained HAZ), it was the lowest. The 18CrNiMo7-6 steel has attracted attention as well [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…P91 is one of the creep-resistant steel for pipes and vessels in the power generation industry. Lojen and Vuherer [30] found out that the high PWHT temperature could shorten the holding time. At 800 • C, 0.5 h was sufficient in terms of hardness and impact toughness.…”
Section: Introductionmentioning
confidence: 99%